The Role of Vitamins in Pediatric Urinary Tract Infection: Mechanisms and Integrative Strategies - Joanna Wróblewska; Hanna Złocińska; Marcin Wróblewski; Jarosław Nuszkiewicz; Alina Woźniak (Biomolecules)
Urinary tract infections (UTI) are among the most frequent bacterial infections in children, representing a significant cause of morbidity with potential long-term complications, including renal scarring and chronic kidney disease. This review explores the multifaceted roles of vitamins A, D, E, and C in the prevention and management of pediatric UTI. Vitamin A supports mucosal barrier integrity and immune modulation, reducing pathogen adhesion and colonization. Vitamin C exhibits antioxidant and antimicrobial properties, acidifying urine to inhibit bacterial growth and enhancing the efficacy of antibiotics. Vitamin D strengthens innate immunity by promoting antimicrobial peptide production, such as cathelicidins, and improves epithelial barrier function, while vitamin E mitigates oxidative stress, reducing renal inflammation and tissue damage. The interplay between oxidative stress, immune response, and nutritional factors is emphasized, highlighting the potential of these vitamins to restore antioxidant balance and prevent renal injury. Complementary strategies, including probiotics and phytotherapeutic agents, further enhance therapeutic outcomes by addressing microbiome diversity and providing additional antimicrobial effects. While these approaches show promise in mitigating UTI recurrence and reducing dependence on antibiotics, evidence gaps remain regarding optimal dosing, long-term outcomes, and their integration into pediatric care. By adopting a holistic approach incorporating vitamin supplementation and conventional therapies, clinicians can achieve improved clinical outcomes, support antibiotic stewardship, and reduce the risk of renal complications in children with UTI.